Assembly dynamics of a large space modular satellite antenna. (December 2019) - Li, Ke; Tian, Qiang; Shi, Junwei; Liu, Dali
Highlights: A novel computation and optimization methodology is proposed for studying a space antenna assembly dynamics. An efficient particle swarm optimization algorithm is used to optimize the assembly manipulator joint trajectories. The oriented bounding box contact detection method is used to avoid contact problems. After completing assembly the satellite base attitude disturbance is minimized by using the optimized trajectories. Abstract: The autonomous assembly technology can be used to construct large space structures such as space telescopes, satellite antennas and space stations. A novel computation methodology to study the assembly dynamics of a large space modular satellite antenna is proposed. The system rigid body and flexible body are respectively described by the natural coordinate formulation (NCF) and the absolute nodal coordinate formulation (ANCF). A parameterized inverse kinematics resolution method is used to evaluate the arm joint rotation angles of a rigid assembly manipulator with 7 degree-of-freedom (DOF). To minimize the disturbance of the floating satellite base attitude, an efficient particle swarm optimization (PSO) algorithm with Latin hypercube sampling skill (LHS-PSO) is used to find the optimized arm joint trajectories of the assembly manipulator arms. In the optimization process the oriented bounding box (OBB) contact detection method is also embedded to eliminate the trajectories which may lead to the arm-satellite or arm-arm impact problems. Finally, two numerical examples are provided to validate the proposed computation methodology. The results show that the satellite base attitude almost return back to its initial state after completing the assembly process by using the optimized joint trajectories.